2020
DOI: 10.1007/s11162-020-09615-7
|View full text |Cite
|
Sign up to set email alerts
|

Taken for Granted? Effects of Loan-Reduction Initiatives on Student Borrowing, Admission Metrics, and Campus Diversity

Abstract: In recent decades, several dozen colleges and universities have instituted loan-reduction initiatives (LRIs), such as "no-loan" programs. Institutions frequently cast such initiatives as efforts to increase socioeconomic diversity on campus. Using a difference-indifferences analytic strategy with national institution-level data, we examine the effect of LRI adoption at 54 institutions on three sets of outcomes: student borrowing, admission metrics, and campus diversity. Our analysis suggests LRIs decreased ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Next, we added measures of an institution's enrollment funnel and practices: (1) percentage of applicants admitted, which approximates institutional prestige; (2) count of applications, which measures the volume an admissions office processed (logged); and (3) a binary variable indicating whether an institution used a no-loan program, which accounts for the possibility that larger scale changes to admissions or aid practices might be associated with particular sieves. We gathered data on no-loan programs from Bennett, Evans, and Marsicano (2021) and institutional websites.…”
Section: Analytic Methodsmentioning
confidence: 99%
“…Next, we added measures of an institution's enrollment funnel and practices: (1) percentage of applicants admitted, which approximates institutional prestige; (2) count of applications, which measures the volume an admissions office processed (logged); and (3) a binary variable indicating whether an institution used a no-loan program, which accounts for the possibility that larger scale changes to admissions or aid practices might be associated with particular sieves. We gathered data on no-loan programs from Bennett, Evans, and Marsicano (2021) and institutional websites.…”
Section: Analytic Methodsmentioning
confidence: 99%
“…These policies assure some or all students that they will either receive no student loans in their financial aid package or receive no loans above a specified amount. Prior research has shown that such policies can result in slight increases in the enrollment of students from low-income backgrounds at private institutions (Bennett et al, 2020;Hillman, 2013), although such findings are not universal (Rosinger et al, 2018). Since there is overlap in the time periods during which institutions adopted test-optional policies and the establishment of ''no-loan'' and ''loan cap'' policies, it is valuable to control for adoption of such initiatives.…”
Section: Control Measuresmentioning
confidence: 99%
“…Since there is overlap in the time periods during which institutions adopted test-optional policies and the establishment of ''no-loan'' and ''loan cap'' policies, it is valuable to control for adoption of such initiatives. The listing of ''no-loan'' and ''loan cap'' institutions and their enactment year comes from Bennett et al (2020).…”
Section: Control Measuresmentioning
confidence: 99%